Assesment of (Mn, Co)33O4 powders for possible coating material for SOFC/SOEC interconnects. Issue 1 (January 2016) - Szymczewska, D.; Molin, S.; Venkatachalam, V.; Chen, M.; Jasinski, P.; Hendriksen, P.V.
Abstract: In this work (Mn, Co)3 O4 spinel powders with different Mn:Co ratio (1:1 and 1:2) and from different commercial suppliers are evaluated for possible powder for production of interconnect coatings. Sinterability of the powders is evaluated on pressed pellets sintered in oxidizing and in reducing/oxidizing atmospheres. For selected powder, coatings are then prepared by the electrophoretic deposition method on Crofer 22 APU stainless steel coupons. Effects of dispersant/iodine content and deposition voltage and times are evaluated. Thickness as a function of deposition parameters is described. Results show that with appropriate powder it is possible to produce adherent protective coating with a well-controlled thickness.